Mrs. Moneypenny's Financial Advice for Independent Women - Moneypenny, Mrs.; McGregor, Heather (London Portfolio Penguin, 2014)
Get a money makeover from the legendary FT columnist, Mrs Moneypenny, author of Mrs Moneypenny's Careers Advice for Ambitious Women. Why do personal finances present such a hurdle for women? And what can we do about it? In her bestselling book Mrs Moneypenny's Careers Advice for Ambitious Women, Mrs Moneypenny stressed the importance of financial literacy and introduced the idea of a 'financial finish line' - or how much money you need in your lifetime. But how do you know what 'enough' looks like? And how do you get there? In this essential and punchy guide, the hilarious and wise Mrs Moneypenny shows you how to set your own financial finish line, and then how to go about reaching it. From increasing your income to cutting your grocery bills, from starting a business to saving a pension, she gives practical, easy ways to think about your money and take control of your life. Whether you're struggling to remember what interest rate you are paying on your mortgage, or are an entrepreneur trying to raise the finance for your business, this book will inspire you, inform you, and above all, empower you.
Include Notes and Resources.
Financial Advice for Independent Women.
Keywords: Women - Finance -- Women Personal Finance -- Personal Finance - Women -- Women